2020
DOI: 10.1038/s41467-020-16505-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of a DNA vaccine candidate for COVID-19

Abstract: The coronavirus family member, SARS-CoV-2 has been identified as the causal agent for the pandemic viral pneumonia disease, COVID-19. At this time, no vaccine is available to control further dissemination of the disease. We have previously engineered a synthetic DNA vaccine targeting the MERS coronavirus Spike (S) protein, the major surface antigen of coronaviruses, which is currently in clinical study. Here we build on this prior experience to generate a synthetic DNA-based vaccine candidate targeting SARS-Co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
600
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 579 publications
(649 citation statements)
references
References 44 publications
17
600
0
8
Order By: Relevance
“…Multiple studies employing a variety of vaccine formulations and modalities have now demonstrated that SARS-CoV-2 viral neutralization titers in small animals including mice and guinea pigs are predictive of immunogenicity in macaques and humans ( Figure 5E) [17][18][19][20]22,23,[33][34][35][36][37][40][41][42][43]45 . Despite promising immunogenicity in several cases, all of the above liquid formulations were either refrigerated or frozen prior to use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies employing a variety of vaccine formulations and modalities have now demonstrated that SARS-CoV-2 viral neutralization titers in small animals including mice and guinea pigs are predictive of immunogenicity in macaques and humans ( Figure 5E) [17][18][19][20]22,23,[33][34][35][36][37][40][41][42][43]45 . Despite promising immunogenicity in several cases, all of the above liquid formulations were either refrigerated or frozen prior to use.…”
Section: Discussionmentioning
confidence: 99%
“…Over 150 vaccine candidates are under development globally 16 . Some vaccine candidates that have entered rapidly into clinical phase testing include mRNA vaccine candidates by Moderna (mRNA-1273), BioNTech (BNT162b1) 17 , and CureVac (CVnCoV), a Chimpanzee Adenovirus vector vaccine by University of Oxford and AstraZeneca (ChAdOx1-S) 18 , a non-replicating adenovirus type-5 (Ad5) vaccine by Cansino (Ad5-nCoV) 19 , a DNA vaccine by Inovio (INO-4800) 20 , inactivated virus vaccines by Sinovac (PiCoVacc) 21 and Bharat Biotech (COVAXIN), a native like trimeric subunit spike protein vaccine by Clover Biopharmaceuticals /GSK/Dynavax (SCB-2019), and a full length recombinant glycoprotein nanoparticle vaccine by Novavax (NVX-CoV2373) 16,22 .…”
Section: Introductionmentioning
confidence: 99%
“…To characterize the viral DNA of the sMVA vectors by PCR, CEF were seeded in 6-well plate tissue culture format and at 70-90% con uency infected at 5 MOI with sMVA or wtMVA. DNA was extracted at [16][17][18][19][20][21][22][23][24] hours post infection by the DNA Easy Blood and Tissue Kit (Qiagen) according to the manufacturer's instructions. All PCR reactions were performed with Phusion polymerase (ThermoFischer Scienti c).…”
Section: Pcr Analysismentioning
confidence: 99%
“…The urgent need of an effective SARS-CoV-2 vaccine, to contain the worldwide pandemic and prevent new viral outbreaks, has led to a global effort involving a wide range of vaccine technologies. These include genetic-based (mRNA and DNA) principles 16,17 , replicating/non-replicating viral vectors (measles 18 , adenovirus 19,20 , baculovirus) recombinant proteins or peptides 21 , virus-like particles (VLPs)/nanoparticles or inactivated and live-attenuated viral vaccines [22][23][24] . In fact, more than 120 SARS-CoV-2 candidate vaccines are currently registered by WHO, of which 21 are currently undergoing clinical testing 25 .…”
Section: Introductionmentioning
confidence: 99%